EFEKTIVITAS SENAM PAGI SEBAGAI UPAYAH MENINGKATKAN KESEHATAN ANAK USIA DINI DI SEKOLAH DASAR - Nindia wulandari; Haifaturrahmah; Inang Irma Rezkillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The decline in physical activity levels among school-age children is a global issue that impacts their physical and psychosocial health. The lack of physical activity in schools can exacerbate sedentary lifestyles, contributing to an increased risk of chronic diseases in the future. This study aims to analyze the effectiveness of morning exercise as a school-based intervention to improve physical fitness, fundamental motor skills, cognitive function, and psychosocial well-being in elementary school children. The method used is a Systematic Literature Review (SLR), gathering data from articles published between 2021 and 2025 through searches in databases such as Scopus, PubMed, and Google Scholar. Selected articles were narratively analyzed using qualitative data analysis techniques to identify emerging patterns in research related to the impact of morning exercise on children. The results indicate that morning exercise significantly improves cardiorespiratory endurance, muscle strength, and body composition, as well as enhances fundamental motor skills and increases concentration and on-task behavior. Additionally, morning exercise contributes to reducing anxiety and stress, while improving social interaction and psychosocial well-being. Based on these findings, morning exercise proves to be an effective and easily applicable intervention to support both physical and psychosocial health in elementary school children.